THE DYSMENORRHEA EFFECT OF ARCHERS PERFORMANCE ON ARCHERY SPORTS - Fatah Nurdin; Yuliasih; Sudradjat Wiradihardja (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to determine the impact of dysmenorrhea on archers' performance in archery at UNJ, the factors that influence dysmenorrhea and the prevention and treatment of dysmenorrhea. The research method used is a descriptive method with a survey technique, namely analyzing the impact of dysmenorrhea on the performance of archers in the archery sport of UNJ. The research was conducted in the archery field of FIK UNJ in August 2021. The population is female archers at the UNJ archery club, totaling 50 people. The sampling technique uses quota sampling, namely the technique of determining samples from the population that have certain characteristics up to the number (quota) What is desired with this research sample is female archery athletes who have experienced puberty or menstruation and have practiced archery for at least six months with a sample of 20 people. The results of this study are that there is no significant difference in the results of archery when experiencing dysmenorrhea or when not experiencing dysmenorrhea. Thus, the condition of dysmenorrhea did not affect the scores of archery athletes at UNJ.